2021
DOI: 10.1029/2021jf006109
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Modeling of Overhanging Riverbank Stability

Abstract: induces salt-marsh loss (Deegan et al., 2012) and thereby affects the global carbon cycle (Kirwan & Mudd, 2012), and modulates the diversity of fluvial habitats (Piégay et al., 1997). According to the driving forces, bank retreat is commonly classified into flow-driven bank erosion and gravity-driven bank collapse (Simon et al., 2000;Thorne, 1982), and the latter can be further classified as slide and cantilever failures. Cantilever failure is usually observed when sediment entrainment by surface and seepage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
(122 reference statements)
1
12
0
Order By: Relevance
“…Extending the experimental analysis to a broader range of values of the ratio H w / H b , K. Zhang et al. (2021) further pointed out the need to include water content variation when predicting shear or toppling failure. Their experimental framework provides a new way to predict failure patterns by combining hydraulic and geotechnical control factors.…”
Section: Mechanisms Leading To Bank Retreatmentioning
confidence: 99%
See 4 more Smart Citations
“…Extending the experimental analysis to a broader range of values of the ratio H w / H b , K. Zhang et al. (2021) further pointed out the need to include water content variation when predicting shear or toppling failure. Their experimental framework provides a new way to predict failure patterns by combining hydraulic and geotechnical control factors.…”
Section: Mechanisms Leading To Bank Retreatmentioning
confidence: 99%
“…Midgley et al (2013) reported that seepage erosion became temporarily restricted after bank collapse, since the collapsed bank soil blocked flow pathways and limited particle mobilization. From a morphodynamic perspective, collapsed bank soil abruptly alters the local topography and the flow resistance of the near-bank channel bed (K. Zhang et al, 2021), possibly generating complex turbulence at the bank toe and affecting the cross-sectional evolution of channels. Based on three-dimensional flow field observations, C. Hackney et al (2015) stated that collapsed bank soil may also deflect flow onto the bank, thus enhancing bank erosion rate.…”
Section: Collapsed Bank Soilmentioning
confidence: 99%
See 3 more Smart Citations